EVALUASI KEBIJAKAN PERATURAN WALIKOTA PROBOLINGGO NOMOR 9 TAHUN 2021 TENTANG SISTEM DAN TATA CARA PENERIMAAN PESERTA DIDIK DI KOTA PROBOLINGGO - Sibro Malisi; Hadi Susanto; Sri Mulyani (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This study aims to find out the policy evaluation of Probolinggo Mayor Regulation Number 9 of 2021 concerning the System and Procedures for Admission of Students in Probolinggo City (the case of student acceptance through a special selection for SMP Negeri 10 Probolinggo City). The approach used in this study is descriptive qualitative with data collection methods consisting of observation, documentation, and interviews. The implementation of the policy of Probolinggo Mayor Regulation Number 9 of 2021 concerning the System and Procedures for Admission of Students in Probolinggo City is not effective because there are implementations of policies that are not in accordance with the expectations of policy making. Policy implementation is quite efficient because the efforts made by policy makers and implementers, in this case SMP Negeri 10 Probolinggo, have been optimal. The positive impact is as a learning from the Probolinggo City Government regarding the implementation of student admissions through special selection, while the negative impact is the existence of strong protests from a number of people which are contained in various mass media. Acceptance of students through special selection conceptually will improve the quality of education.